Development of educational leadership in research university through community of practices among professors - Ismail, Ismi Arif; Silong, Abu Daud; Asmiran, Soaib; Hassan, Zaharah (Elsevier, 2011)
We are using the COP (Community of Practice) model as a conceptual framework to explore professors’ experiences and to understand educational leadership in Research University (RU). This research utilized the qualitative method, interviewing twenty professors from universities in Malaysia and overseas as well as conducting two focus group interviews with university leaders from two universities. Interviews were recorded and transcribed verbatim and the data were categorized into themes. The findings indicated that through COP of professors, we can understand the process of how they conduct their jobs such as in teaching, research and consultancy. Through the COP, we can develop educational leadership for RU.